IDENTIFIKASI PRASYARAT TRANSFORMASI SISTEM MANAJEMEN RISET PERGURUAN TINGGI INDONESIA MENUJU WORLD CLASS UNIVERSITY - Yuli Sukmawati; Anas Fauzi; Hari Wijayanto (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
This research was conducted to identify enabling factors for an effective transformation of Higher Education Institution’s (HEI’s) research management system in Indonesia towards World Class University (WCU) status. Three clusters of HEIs, particularly PTN-bh WCU, PTN-bh and PTN Non-bh produced exceptional studies output and outcome (citation) wherein PTN-bh WCU produced the best quantity of publications and citations. The data analysis technique in this study used a comparative analysis of research mapping and Biplot analysis. The result of the Biplot analysis indicate that research infrastructure as essential enabler for all HEIs. Biplot also displays the important enabler that affected research productivity in PTN Non-bh (research human resources, academic collaboration), PTN-bh (research funding, insentive, PTN-bh WCU (academic culture, system and management research). Keywords: research management system, enabler factors, transformation, world class university, Biplot analysis